IMPROVEMENT OF AGRICULTURAL TERMS IN UZBEKISTAN AND RUSSIAN - Burkhonova Guzal Mukhammadiyevna (Modern American Journals, 2025)
This article analyzes the formation and stages of development and improvement of agricultural terminology in the Uzbek and Russian languages based on a systematic approach. It considers the etymology of terms, word formation methods, semantic features, and linguistic inconsistencies encountered in the translation process. Also, existing specialized dictionaries are thoroughly analyzed, and ways to improve them based on modern scientific and technical requirements are shown. Lexicographic approaches are aimed, in particular, at increasing the efficiency of the interdisciplinary translation process, and the results of the article are of practical importance for translators, linguists, and compilers of specialized dictionaries. The systematic development of agricultural terminology, the accuracy of bilingual alternatives, and consistent lexicographic processing serve to increase the efficiency of scientific and technical information exchange.
Keywords: Agricultural terminology, Uzbek language, Russian language, evolution of terms, translation theory, lexicography, word formation, interdisciplinary translation, semantic analysis, linguistic inconsistency.